O-027 Antithrombotic states and outcomes in patients with aneurysmal subarachnoid hemorrhage. (12th July 2011) - Hui, F; Schuette, A; Spiotta, A; Lieber, M; Moskowitz, S; Dion, J; Tong, F; Barrow, D; Cawley, M
Abstract : Introduction: Antithrombotic states are encountered frequently, either due to medical therapy or by pre-existent pathologic states, and may affect the severity of hemorrhagic strokes such as aneurysmal subarachnoid hemorrhages. Cerebrovascular specialists analyzed a 2-year period of subarachnoid hemorrhage data in order to determine the effects of antithrombotic states on the outcomes of patients with aneurismal subarachnoid hemorrhage. Methods: This is a retrospective review of 365 patients who experienced aneurysmal subarachnoid hemorrhage at Emory University over a 2-year period. The patients were grouped into those with and without an antithrombotic state at time of hemorrhage and were stratified according to presentation, clinical grades, outcomes, need for cerebrospinal fluid diversion and the development of vasospasm. CT of the head was assessed for bleed pattern and Modified Fisher Grade (mF). Patients were excluded if no aneurismal source was subsequently discovered. Results: There is a strong association between antithrombotic states and outcomes as assessed by modified Rankin Scale (p<0.0001). Patients have worse outcomes even when adjusting for the amount of hemorrhage as assessed by modified Fisher Grade and Hunt and Hess Scores (p<0.001). There was no significant difference between the two groups in terms of presentation grades Hunt and Hess score (HH) (p=0.44), modified Fisher Grade (p=0.55), incidence of vasospasm (p=0.30), or need for ventricular peritoneal shunting (p=0.85). Conclusion: Patients in antithrombotic states presenting with aneurysmal subarachnoid hemorrhage have worse outcomes without a significant difference in presentation grades.